2011
DOI: 10.1007/s10620-010-1536-3
|View full text |Cite
|
Sign up to set email alerts
|

miR-137 Is Frequently Down-Regulated in Gastric Cancer and Is a Negative Regulator of Cdc42

Abstract: miR-137 is frequently down-regulated in gastric cancer and is a negative regulator of Cdc42.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 17 publications
(20 reference statements)
6
107
2
Order By: Relevance
“…Previous studies have demonstrated that a low expression of miR-137 inhibits cell growth in vivo and in vitro through G 1 phase cell cycle arrest, and impairs cell migration and invasion (7,27). To investigate the effect of miR-137 on NSCLC cell growth, the colony forming and proliferation ability of cells was determined using soft agar colony formation assays and MTT assays, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that a low expression of miR-137 inhibits cell growth in vivo and in vitro through G 1 phase cell cycle arrest, and impairs cell migration and invasion (7,27). To investigate the effect of miR-137 on NSCLC cell growth, the colony forming and proliferation ability of cells was determined using soft agar colony formation assays and MTT assays, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…49 For example, it has been shown that RhoA is target of miRNA-155 50,51 and miRNA-125a-3p; 52 RhoB is a target of miRNA- 21; 53 RhoBTB1 is a target of miRNA-31; 54 and Cdc42 is a target of miRNA-29 55 and miRNA-137. 56 Sometimes the same miRNA can target 2 different Rho GTPases. miRNA-185 has been reported to decrease the levels of RhoA and Cdc42, leading to inhibition of proliferation in human colorectal cancer cells.…”
Section: 43mentioning
confidence: 99%
“…In hepatocellular carcinoma, miR-224 promotes cell proliferation, migration and invasion, and inhibited apoptosis by regulating CDC42 expression (49). In gastric cancer, CDC42 was demonstrated to be a direct gene of miR-137 (50). In NSCLC, miR-25 and miR-137 were demonstrated, by targeting CDC42, to be important regulators in initiation and progression and NSCLC (51,52).…”
Section: Cdc42 Is Involved In Mir29a-induced Effects In Nsclc Cellsmentioning
confidence: 99%